Democracy Today: Assessing Democracy Phenomenon in Indonesia - istriyani, ratna (POLITEA, 2018)
Democracy as a political and the government system has demonstrated its existence in the history of the world. This existence can be seen from the many countries that implement it, especially Indonesia. The democratic process becomes an interesting phenomenon because it cannot be separated from the dynamics of the community itself.At present the community has entered the digital era, that the utilization of information and communication technology are massive. One phenomenon of concern is the widespread use of social media. The reality of the utilization of social media not only showed the trend of community interaction and communication but also the trend of political participation which correlates with the sustainability of democracy in Indonesia. At least, it has happened in the last decades, where political figures have been using social media as a channel to construct personal image. On the other hand, social media for civil society is as a new media (alternative media) in channeling aspirations, support, and even criticism to political and government figures.Social media trends also cannot be separated from the figure of young people as massive users of these contemporary products. Even social media is a preference for young people to participate in upholding democratization in Indonesia. It can be seen from the posts or their responses to the socio-political conditions in this country through their account lines and the number of comments they wrote on the accounts of a number of political and government figures.Keywords: democracy, social media, youth.